Incremental Theory of Intelligence Moderated the Relationship between Prior Achievement and School Engagement in Chinese High School Students - Li, Ping; Zhou, Nan; Zhang, Yuchi; Xiong, Qing; Nie, Ruihong; Fang, Xiaoyi (Frontiers in Psychology, 2017)
School engagement plays a prominent role in promoting academic accomplishments. In contrast to the relative wealth of research that examined the impact of students’ school engagement on their academic achievement, considerably less research has investigated the effect of high school students’ prior achievement on their school engagement. The present study examined the relationship between prior achievement and school engagement among Chinese high school students. Based on the Dweck’s social-cognitive theory of motivation, we further examined the moderating effect of students’ theories of intelligence (TOIs) on this relationship. A total of 4036 (2066 girls) students from five public high school enrolled in grades 10 reported their high school entrance exam achievement in Chinese, Math and English, school engagement, and TOIs. Results showed that (a) students’ prior achievement predicted their behavioral, emotional, and cognitive engagement, respectively, and (b) the association between prior achievement and behavioral, emotional, and cognitive engagement is strong for students with an incremental theory but not for those with an entity theory in the emotional and cognitive engagement. These findings suggest that prior achievement and incremental theory were implicated in relation to adolescents’ school engagement. Implications and future research directions were discussed.